Impact of hormonal status on outcome of ductal carcinoma in situ treated with breast-conserving surgery plus radiotherapy: Long-term experience from two large-institutional series. (June 2017) - Meattini, Icro; Saieva, Calogero; Bastiani, Paolo; Martella, Francesca; Francolini, Giulio; lo Russo, Monica; Paoletti, Lisa; Doria, Morena; Desideri, Isacco; Terziani, Francesca; De Luca Cardillo, Carla; Bendinelli, Benedetta; et al.
Abstract: Background: Ductal carcinoma in situ (DCIS) is a heterogeneous disease, for which the best adjuvant treatment is still uncertain. Many attempts of risk-groups stratification have been made over time, developing prognostic scores to predict risk of local recurrence (LR) on the basis of features such as age, final surgical margins (FSM) status, grade, and tumor size. The aim of our analysis was to evaluate the patterns of recurrence from a two large-institutional retrospective series. Patients and methods: We collected data on 457 patients treated with BCS and adjuvant RT between 1990 and 2012. Final analysis was performed on 278 patients, due to missing data about hormonal status (HS). Patients were treated at the Radiation Oncology Unit of the University of Florence (n = 195), and S. Maria Annunziata Hospital (n = 83) (Florence, Italy). Results: At a median follow up time of 10.8 years (range 3–25), we observed 20 LR (7.2%). The 5-year and 10-year LR rates were 4.9% and 10.2%, respectively. At Cox regression univariate analysis, estrogen receptor (ER) positive status (p = 0.001), HS positive (p = 0.003), and FSM <1 mm (p = 0.0001) significantly impacted on LR. At Cox regression multivariate analysis positive ER status maintained a protective role (p = 0.003), and FSM status <1 mm its negative impact (p = 0.0001) on LR rate. Conclusions: Our experience confirmed the wide heterogeneity of DCIS. Inadequate FSM and negative ER status negatively influenced LR rates. Tumor biology should be integrated in adjuvant treatment decision-making process. Highlights: DCIS is a heterogeneous disease, and the best adjuvant treatment is still uncertain. Use of adjuvant treatments in the main trials showed significant improvement on local control in selected patients. Inadequate final margins status and negative hormonal status negatively impacted on local recurrence rate. DCIS biology should be integrated in a highly multidisciplinary counseling scenario.